Chronic myeloid leukemia blast crisis presented with AML of t(9;22) and t(3;14) mimicking acute lymphocytic leukemia. Issue 8 (19th June 2019) - Liu, Keyu; Hu, Jintian; Wang, Xueqin; Li, Li
Abstract: Background: Clinically, 90%‐95% of cases of CML have the characteristic t(9;22) (q34.1;q11.2) translocation that leads to the Philadelphia (Ph) chromosome. Rarely, patients with CML can present directly in a blast crisis (BC). While most blast crises are of myeloid origin, myeloid BC with ALL‐like morphologic features and Ph‐positive acute myeloid leukemia (AML) is rare, especially at the time of CML diagnosis. Case presentation: A 20‐year‐old man presented with Ph chromosome‐positive AML mimicking acute lymphocytic leukemia (ALL). Bone marrow (BM) aspiration revealed AML with ALL‐like morphologic features. The results of the immunophenotypic analysis suggested AML. Cytogenetic analysis of the BM cells revealed a 46, XY, t(3;14)(q21;q32), t(9;22)(q34;q11.2)[20] karyotype. Thus, we called the condition AML mimicking ALL. The patient was diagnosed with myeloid BC based on the combination of clinical, cytologic, and cytogenetic studies. Conclusion: To date, no case reports of a patient diagnosed with CML BC presented with Ph chromosome‐positive AML mimicking ALL have been reported. We present the case given its rarity, easy misdiagnosis, and poor prognosis. It is important to combine clinical, cytologic, and cytogenetic analyses in distinguishing CML BC from de novo AML with the t(9;22)，and further cases should be accumulated to explore how to improve the prognosis of the patients.